The multifaceted roles of NLRP3-modulating proteins in virus infection - Harris, James; Borg, Natalie A. (Frontiers in Immunology, 2022)
The innate immune response to viruses is critical for the correct establishment of protective adaptive immunity. Amongst the many pathways involved, the NLRP3 [nucleotide-binding oligomerisation domain (NOD)-like receptor protein 3 (NLRP3)] inflammasome has received considerable attention, particularly in the context of immunity and pathogenesis during infection with influenza A (IAV) and SARS-CoV-2, the causative agent of COVID-19. Activation of the NLRP3 inflammasome results in the secretion of the proinflammatory cytokines IL-1β and IL-18, commonly coupled with pyroptotic cell death. While this mechanism is protective and key to host defense, aberrant NLRP3 inflammasome activation causes a hyperinflammatory response and excessive release of cytokines, both locally and systemically. Here, we discuss key molecules in the NLRP3 pathway that have also been shown to have significant roles in innate and adaptive immunity to viruses, including DEAD box helicase X-linked (DDX3X), vimentin and macrophage migration inhibitory factor (MIF). We also discuss the clinical opportunities to suppress NLRP3-mediated inflammation and reduce disease severity.